New Challenges in Seed Biology - Basic and Translational Research Driving Seed Technology 2016
DOI: 10.5772/64420
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming: New Comprehensive Approaches for an Old Empirical Technique

Abstract: Seed priming is a pre-sowing treatment which leads to a physiological state that enables seed to germinate more efficiently. The majority of seed treatments are based on seed imbibition allowing the seeds to go through the first reversible stage of germination but do not allow radical protrusion through the seed coat. Seeds keeping their desiccation tolerance are then dehydrated and can be stored until final sowing. During subsequent germination, primed seeds exhibit a faster and more synchronized germination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
180
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(231 citation statements)
references
References 168 publications
3
180
1
10
Order By: Relevance
“…In addition to planting dry seeds, seeds can be 'primed' with water, an enhancement method that might improve seed performance under stress conditions such as drought or when freshly harvested or aged seeds are used which might fail to germinate (Lutts et al 2016). Harris et al (1999) demonstrated how simple soaking seeds in water before sowing can increase the speed of germination and emergence, leading to better crop stands, and allow seedlings to grow much more vigorously.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to planting dry seeds, seeds can be 'primed' with water, an enhancement method that might improve seed performance under stress conditions such as drought or when freshly harvested or aged seeds are used which might fail to germinate (Lutts et al 2016). Harris et al (1999) demonstrated how simple soaking seeds in water before sowing can increase the speed of germination and emergence, leading to better crop stands, and allow seedlings to grow much more vigorously.…”
Section: Introductionmentioning
confidence: 99%
“…The general physiological effects of hydropriming have recently been reviewed (Lutts et al, 2016). The increase of the water potential in seeds caused by the soaking allows biochemical processes preparing the seed for germination to initiate: Mobilisation of energy and nutrients through the activity of amylases and other metabolic enzymes, and repair of cellular damage that occurred during storage of the seed (DNA, membranes, organelles, redox balances).…”
Section: Theoretical Context Of Resultsmentioning
confidence: 99%
“…Seed coating technologies are sophisticated and expensive (Sharma et al, 2015). Seed priming emerged as the most common method of presowing treatments (Parera & Cantliffe, 1994;Jisha et al, 2013;Soleimanzadeh, 2013;Paparella et al, 2015;Lutts et al, 2016;Wojtyla et al, 2016).…”
Section: Possible Alternativesmentioning
confidence: 99%
“…Slow and non-uniform germination of seeds induced the requirement of water-based seed priming. Hydropriming is a very simple, cost-effective, and eco-friendly technique which basically involves soaking seeds in water for a pre-determined time followed by re-drying to their initial moisture content (Farooq et al, 2006;Lutts et al, 2016). Submergence can also be performed in distilled water with or without aeration.…”
Section: Hydroprimingmentioning
confidence: 99%